The Implementation of Management Accounting Practices (Maps): Managers’s Perception: MANAGERS’S PERCEPTION - Magdalena, Renna (International Journal of Scientific Research and Management (IJSRM), 2020)
The purpose of this study is to investigate the implementation of Management Accounting Practices (MAPs) in Food Industries in Bali Island. MAPs in this Study will be measured by Costing Systems, Performance Measurement System (PMS), Decision Support System (DSS). The data for this study was obtained from questionnaire distributed to 100 Finance and Accounting managers. Descriptive Statistics frequency of using MAPs will be the main discussion of this study. Further interviews were also conducted to get more detailed picture of MAPs. Current state of MAPS at Food Industries may provide directions to other industry players regarding current MAPS trends and future trends. Accountant educators can get an idea of managerial accounting skills to prioritize for teaching prospective accountants.